Advances in high‐throughput mass spectrometry in drug discovery. Issue 1 (14th December 2022) - Dueñas, Maria Emilia; Peltier‐Heap, Rachel E; Leveridge, Melanie; Annan, Roland S; Büttner, Frank H; Trost, Matthias
Abstract: High‐throughput (HT) screening drug discovery, during which thousands or millions of compounds are screened, remains the key methodology for identifying active chemical matter in early drug discovery pipelines. Recent technological developments in mass spectrometry (MS) and automation have revolutionized the application of MS for use in HT screens. These methods allow the targeting of unlabelled biomolecules in HT assays, thereby expanding the breadth of targets for which HT assays can be developed compared to traditional approaches. Moreover, these label‐free MS assays are often cheaper, faster, and more physiologically relevant than competing assay technologies. In this review, we will describe current MS techniques used in drug discovery and explain their advantages and disadvantages. We will highlight the power of mass spectrometry in label‐free in vitro assays, and its application for setting up multiplexed cellular phenotypic assays, providing an exciting new tool for screening compounds in cell lines, and even primary cells. Finally, we will give an outlook on how technological advances will increase the future use and the capabilities of mass spectrometry in drug discovery. Abstract : This Review summarizes advantages and disadvantages of high‐throughput mass spectrometry techniques used in drug discovery and discusses how technological advances could increase the capabilities of mass spectrometry in drug discovery in the future.